Multidimensional Connectivity : Benefits, Risks, and Policy Implications for Europe and Central Asia - Gould, David (World Bank, Washington, DC, 2018)
International connections through trade, foreign direct investment, migration, the Internet, and other channels are critical for the transmission of knowledge and growth and form macroeconomic linkages. But how much knowledge is transmitted to a country is not only the result of the overall level of connectivity, but also to whom a country is connected, as well as how these connections complement each other. For example, being well-connected to an economy with wide-reaching global connections is likely to be a stronger conduit for knowledge transfers than being connected to an isolated economy. Likewise, connections are likely to complement each other. For example, ecommerce is often seen as a benefit of Internet connectivity, but without transport connectivity, ecommerce may not amount to much. This wider definition of connectivity, referred to as multidimensional connectivity, is broadened and explored in this study as it applies to Europe and Central Asia. Focusing on countries from the Europe and Central Asia region, the paper shows that multidimensional connectivity is an economically and statistically important determinant of future economic growth. The paper further discusses the potential risks and transfer of shocks that can result from cross-country economic connectivity. Furthermore, it provides some examples of how policy tools can be designed to leverage the benefits of connectivity channels and mitigate their risks.